IISR Mahima and IISR Rejatha - two high yielding and high quality ginger (Zingiber officinale Rosc.) varieties - Eapen, B Sasikumar, K V Saji, Alice Antony, Johnson K George, T John Zachariah, S J (Journal of Spices and Aromatic Crops, 2003)
IISR Mahima (Acc. 117) and IISR Rejatha (Acc. 35), developed through selection from germplasm at the Indian Institute of Spices Research, Calicut are good quality, high yielding ginger varieties. Maturing in 200 days, IISR Mahima has given an average yield of 23.2 t ha-1 (fresh) with a dry recovery of 23%, essential oil 1.72%, oleoresin 4.48% and fibre content 3.26%. Rhizomes of Mahima are bold and this variety is resistant to root-knot nematode also. IISR Rejatha is a medium duration, bold variety with an average yield of 22.4 t ha-1 (fresh), dry recovery 19%, essential oil 2.36%, oleoresin 6.34% and fibre content 4.0%.